2009
DOI: 10.2298/psi0903273b
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic and cultural factors of low scholastic achievement of Roma children

Abstract: This study investigated environmental influences on scholastic achievement of first-grade elementary school students. A total of 149 (average age 81 months) first-grade children were classified in three groups. The first group comprised of 52 Roma children. Two other groups consisted of 48 non-Roma children classified as children belonging to an average socioeconomic status (SES) group and 49 non-Roma children classified as children belonging to a below-average SES group. All 52 Roma children belonged to a bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 18 publications
2
18
0
1
Order By: Relevance
“…For the Roma group, there are only two concurrent Serbian studies; one focuses on vocabulary development, while the other targets reading comprehension. The first study showed a large difference in vocabulary levels between Roma children and their non‐Roma peers (0.85 standard deviation units [Biro, Smederevac, & Tovilovic, ]). The second study showed a large difference between Roma children and their peers on a national test measuring reading comprehension (1.2 standard deviation units [Baucal, ]).…”
Section: Previous Studies Of Vocabulary and Reading Comprehension In mentioning
confidence: 99%
“…For the Roma group, there are only two concurrent Serbian studies; one focuses on vocabulary development, while the other targets reading comprehension. The first study showed a large difference in vocabulary levels between Roma children and their non‐Roma peers (0.85 standard deviation units [Biro, Smederevac, & Tovilovic, ]). The second study showed a large difference between Roma children and their peers on a national test measuring reading comprehension (1.2 standard deviation units [Baucal, ]).…”
Section: Previous Studies Of Vocabulary and Reading Comprehension In mentioning
confidence: 99%
“…It is important to note that almost all of the studies concerning the relationship between SES and EF were conducted in developed countries (e.g., Noble et al, 2005; Farah et al, 2006; Biro et al, 2009). Noble et al (2007) suggest that it is important to investigate if these results could be generalized to other cultures in which there is more heterogeneity in the distribution of SES across the population.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence also shows that deprived environments, in which the poorest children grow, affect the achievement on different cognitive tests and therefore have a negative impact on academic achievement, which in turn can "trigger" dropout (Baucal, 2006;Biro, Smederevac & Tovilović, 2009;. Hence, dropout prevention has an important influence on various social outcomes, from poverty reduction to the better social cohesion and health issues (Nacionalni prosvetni savet, 2015;OECD, 2010;Stiglitz, 2012;Wilkinson & Picketi, 2010).…”
Section: Measures In the Dropout Prevention Model Dpm In Serbian Scmentioning
confidence: 99%